Techno-utopianism and the Orient in Russian revolutionary culture - Hellebust, Rolf (University of Nottingham, 2013)
The magnitude of the hopes pinned on technology in early twentieth-century Russia was directly proportional to its relative backwardness in this area. The nation saw itself on the brink of an historic clash between the age-old ways of the Slavic peasant and the advances of the industrialized West. In Russia the debate over technological progress is intimately involved with the issue of the nation’s relationship with Europe – or in broader terms, the eternal question “East or West?” In the opening decades of the twentieth century this multifarious dichotomy achieves even greater prominence, as evidenced by a range of revolutionary-era writers, from Symbolists such as Blok and Belyi, to proletarian poets such as Gastev, and early Soviet novelists such as Pilnyak, Zamyatin, and Platonov. A key factor in their problematization of the Orientalist (and Bolshevik) dictum of the backward East is a vision of technological apocalypse, rather than progress, in which Russia engages in a Nietzschean struggle to defeat technology by its own means, and thus escape teleology – and history – altogether.